A gastric stump cancer with unusual appearance - Ferdane Sapmaz; Sebahat Basyigit; Metin Uzman; Gulcin Guler Simsek; Tolga Akkan; Yasar Nazligul (Journal of Health Sciences, 2015)
A 60 year old man was referred to our hospital with the chief complaints of abdominal pain and vomiting. He underwent a distal gastrectomy with a Billroth II gastrojejunostomy for a peptic ulcer 13 years ago. Esophagogastroduodenoscopy (EGD) did not reveal any gross lesion in the stomach but depigmented areas were seen in the anastomosis line. The histopathology of the anastomotic area revealed poorly differentiated adenocarcinoma. Gastric stump cancers can be polypoid, fungating, ulcerated and diffusely infiltrating tumors respectively. In our case, the appearance of adenocarcinoma was quite different from that described in the classification system.